PENGGUNAAN KOMPUTER UNTUK MENGHITUNG OATA UKUR TANAH DI KALANGAN PARA SURVEYOR - Sunar Rochmadi (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2006)
AbstractThis research aims to gather information of computer uses for landsurveying data calculation in the work field of land surveying andmapping in the Yogyakarta Province and surroundings. The researchfocuses on the actors of computer uses, surveying data types, softwaretypes, and its linkage with the drawing process.This research applies qualitative approach. The chosenresearch subjects are seven land surveyors in Yogyakarta andsurroundings. The data were collected by in-depth interview,participating observation, and document analysis. The data analysisconsists of the processes of categorizing, data reduction, data display,and verification.The research results show that the computer uses for landsurveying data calculation are applied by various levels of surveyor, fromthe lower competency level, Young Surveyor or operator, with seniorhigh-school education background, to the highest level, Main Surveyoror Senior Professional Surveyor. Computer aided calculation is appliedfor all surveying data types, especially mapping framework surveyingdata. traverses and levels. The common software used for surveyingdata calculation is Microsoft Excel, utilizing formulae and functionmenus. The drawing processes of calculation results can be categorizedinto three groups: manual drawing, computer drawing using AutoCADsoftware, and drawing with the integrated program for calculation anddrawing.Keywords: computer uses, land-surveying data, surveying datacalculation.